Co-Constructed Space and The Power of Presents: Unwrapping Relational Identity in the Teenage Bedroom. (2nd September 2017) - Carey, Newson
Abstract: This paper draws on qualitative visual research with 26 teenagers and their parents in East and North London to explore negotiated aspects of domestic space in teenage bedrooms. In addition to examining how collaboration and compromise had helped to shape these spaces, it focuses especially on a key component that contributed to teenagers' material culture at home: that of presents and present-giving. Gifts were a ubiquitous feature of the study's teenage bedrooms. Engaging with the reflexive accounts of teenagers and their parents, as well as the extensive literature on gifts, the article asks how, and to what effect, presents contributed to these material and social worlds. The article argues that in the individualized space of the teenage bedroom, presents can be seen as vectors of co-construction, which, together with other evidence of collaboration, help support less atomized and more relational conceptions of personal identity and selfhood.